2015
DOI: 10.1007/s10096-015-2321-1
|View full text |Cite
|
Sign up to set email alerts
|

First isolation of Coxiella burnetii from clinical material by cell-free medium (ACCM2)

Abstract: A disadvantage in Q fever diagnostics and research is the insensitive and difficult culture of Coxiella burnetii. This intracellular organism can only be isolated using embryonated eggs, animal hosts, or mammalian cell culture. In consequence, it has only been possible to isolate a few strains from human patients. Here, we describe the first isolation of C. burnetii from a clinical specimen using the recently developed cell-free medium acidified citrate cysteine medium 2 (ACCM2). We screened the sera of 217 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…They proposed using two panels of markers to have a better discriminatory power (169). In the literature, there are 17 references for studies that have used this genotyping method, almost all from Europe and mainly among ruminants (66,73,(170)(171)(172)(173)(174)(175)(176)(177)(178)(179)(180)(181)(182)(183)(184). The clone causing the Netherlands outbreak was identified as CbNL01 using this method, and a very similar clone was detected in goats in Belgium (178).…”
Section: Comparative Genomics and Pangenomic Analysismentioning
confidence: 99%
“…They proposed using two panels of markers to have a better discriminatory power (169). In the literature, there are 17 references for studies that have used this genotyping method, almost all from Europe and mainly among ruminants (66,73,(170)(171)(172)(173)(174)(175)(176)(177)(178)(179)(180)(181)(182)(183)(184). The clone causing the Netherlands outbreak was identified as CbNL01 using this method, and a very similar clone was detected in goats in Belgium (178).…”
Section: Comparative Genomics and Pangenomic Analysismentioning
confidence: 99%
“…A subsequent version (ACCM-2) supported improved growth and was shown to be effective for the virulent Nine Mile Phase 1 and Q212 C. burnetii isolates (Omsland et al 2011). It has been demonstrated that C. burnetii can be isolated from a clinical sample using ACCM-2 (Boden et al 2015), but whether ACCM-2 is effective for isolation of all contemporary sequence types is not known.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a recent study, the first isolation of C. burnetii from a clinical specimen using a newly developed cell-free medium, acidified citrate cysteine medium 2 (ACCM2), was described. 39 The sensitivity of this medium is yet unknown, but results may modify the current investigative methods.…”
Section: Culturementioning
confidence: 99%